Are hedonic hunger and health-related quality of life associated with obesity in adolescents? - Meral Koc, Bilge; Kenger, Emre Batuhan; Arslan Yuksel, Ezgi; Ozlu Karahan, Tugce (Frontiers in Nutrition, 2025)
The purpose of the study is to find out the relationship between obesity, hedonic hunger and health-related quality of life (HRQoL). The questionnaire containing items on the sociodemographic characteristics, anthropometric measurements and nutritional habits of individuals (n = 902), the Children’s Power of Food Scale and the KIDSCREEN-10 were used to determine the hedonic hunger and the HRQoL score. Hedonic hunger and HRQoL were evaluated according to the categories, frequency of consumption of sugary drinks and fast food. The females were found to have hedonic hunger more than the males (p < 0.05). Body mass index z-score categories of the adolescents showed that the obese eat more hedonically compared to the underweight and the normal-weight (p < 0.05), and this difference was not observed in the HRQoL scores (p > 0.05). There was a negative correlation between the hedonic hunger status and the HRQoL scores (R = −0.342, p = 0.000). The consumption of sugary drinks and fast food was associated with hedonic hunger and HRQoL scores in certain groups. Hedonic hunger is associated with obesity; hedonic hunger and quality of life are important factors associated with unhealthy food and drink intake.